Pengaruh Film Kartun Berbahasa Inggris sebagai Pengembangan Kosakata pada Kalangan Anak-Anak di Kabupaten Sumenep - Hanifatur Rizqi; Eko Adi Sumitro (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the influence of English cartoon films on the development of children's English vocabulary in Sumenep Regency. In the current era of globalization, English language skills are very important, especially in vocabulary mastery from an early age. This study used a quantitative approach with an experimental design on 60 children aged 6–12 years who were divided into experimental and control groups. Data collection techniques included vocabulary tests, observations, interviews, and questionnaires. The results showed that children who watched English cartoon films regularly experienced a significant increase in their English vocabulary mastery compared to children who were not exposed to the media. The effectiveness of this media is influenced by the frequency of watching, content quality, and parental guidance. Apart from that, cartoon films have been proven not only as entertainment, but also as an effective, fun learning medium, and able to build motivation and positive attitudes towards learning English. This study recommends that parents and educators utilize audiovisual media optimally to support the development of children's language learning.